Targeted therapy of bronchial asthma in children and adolescents: А narrative review - M. S. Matevosova; L. I. Agapitov; I. A. Averina; I. V. Sokolova; S. V. Zotova; R. A. Chernigovskiy (Фармация и фармакология (Пятигорск))
The aim. To evaluate the results of clinical studies on the efficacy and safety of bronchial asthma (BA) therapy with genetically engineered biologicals (GEBP) in children and adolescents.Materials and methods. For writing this review article, a search for full-text publications was conducted in the PubMed database. Studies on the efficacy and safety of biologicals — monoclonal antibodies, in the treatment of BA refractory to therapy with inhaled glucocorticosteroids and beta-2-agonists, in children and adolescents from 2010 to 2025 were analyzed using the following key queries”bronchial asthma”, “monoclonal antibodies”, “anti-IgE antibody”, “anti-IL-receptor antibody”, “anti-thymic stromal lymphopoietin antibody”, “adolescents”, “children”.Results. The observed continuing and steady increase in the incidence of BA, the involvement of several organ systems in the pathological process, the difficulty in choosing treatment tactics, the high cost of therapy, and the need to monitor the patient’s condition place this disease in a special place among modern medical problems. To date, advances in genetic engineering have made it possible to introduce GEBPs — monoclonal antibody drugs, into medical practice as one of the steps in the treatment of poorly controlled and resistant to first-line therapy BA of moderate and severe severity. According to recent clinical studies among children and adolescents, biologicals to varying degrees can affect symptom control, lung function, frequency of exacerbations, requests for emergency medical care and hospitalizations, as well as reducing the dosages of glucocorticosteroids and beta-2-agonists used.Conclusion. To date, positive results have been noted in the use of monoclonal antibodies in the treatment of BA, but clinical trial data among children and adolescents are limited. There is also insufficient information about the consequences of the mechanism of influence of these drugs in relation to long-term inhibition of the immune system and a decrease in the content of eosinophils in the blood serum in the developing child’s body. To formulate a final conclusion, further study of the long-term efficacy and safety of biologicals in pediatric practice is necessary in order to combat this serious public threat.